The DeLone and McLean model for measuring success in online learning systems: Indonesian evidence - Vita Sarasi; Iman Chaerudin; Irhaz Aulianandatama Sundoro (Intelektual Pustaka Media Utama, 2023)
The development of information and communication technology (ICT) during the era of the fourth industrial revolution, the impact of the COVID-19 pandemic in 2020, and the government’s call for large-scale social restrictions have led to the emergence of online learning systems (OLS) in higher education. This study develops a measurement model for the success of OLS based on the DeLone McLean model. Surveys were conducted on a sample of 175 students from domestic and international universities. Data processing used the partial least squares structural equation modeling or PLS-SEM method, and root cause analysis. The results show that platform quality has a positive influence on OLS success, whether mediated by user satisfaction or OLS usage. Social influence has a positive effect on OLS success, mediated by OLS usage. User computer anxiety has a negative effect on OLS success, mediated by user satisfaction. Recommendations to improve OLS success include adjusting internet package rates to make them more affordable, improving signal strength to various locations for better coverage, limiting the number of users in one learning session for more effective OLS, and the need for organizational support in using the right applications.